«Я вернулся в мой город…»: Неизвестный вариант стихотворения О. Э. Мандельштама [“Ia vernulsia v moi gorod...”: An Unknown Version of Osip Mandel’shtam’s Poem] - Dolinina, Anna; Salman, Marina (Slavica Revalensia, 2015)
This is the first publication of a previously unknown version of Osip Mandel’shtam’s poem “Ia vernulsia v moi gorod, znakomyi do slez...” (1930, 1932), which survived in the archive of the famous Russian scholar Arkady Dolinin (1883—1968) (currently located in the Manuscript Division of the National Library of Russia). It has come to us in the spisok (copy) made by an unknown person, who almost certainly met Mandel’shtam in the period between late December 1930 and early January 1931. Although the name of the copyist cannot be established, the text as such is remarkable in the way it differs from the final version. Cf. the final version: Ia vernulsia v moi gorod, znakomyi do slez, Do prozhiok, do detskikh pripukhlykh zhelez. Ty vernulsia siuda – tak glotai zhe skorei Rybii zhir leningradskikh rechnykh fonarei. Uznavai zhe skoree dekabr’skii denek, Gde k zloveshchemu degtiu podmeshan zheltok. Peterburg! ia eshcho ne khochu umirat’: U tebia telefonov moikh nomera. Peterburg! U menia eshcho est’ adresa, Po kotorym naidu mertvetsov golosa. Ia na lestnitse chernoi zhivu, i v visok Udariaet mne vyrvannyi s miasom zvonok, I vsiu noch’ naprolet zhdu gostei dorogikh, Shevelia kandalami tsepochek dvernykh. Cf. the version prepared for publication by Anna Dolinina and Marina Salman: Ia vernulsia v moi gorod, znakomyi do slez, Do prozhilok, do detskikh pripukhshikh zhelez… Ia vernulsia siuda, tak glotai zhe skorei Rybii zhir peterburgskikh rechnykh fonarei… Mne zabyt’-ne zabyt’ tot dekabr’skii denek, Gde k zloveshchemu degtiu primeshan zheltok… Peterburg! Ia eshcho ne khochu umirat’! U menia telefonov tvoikh nomera… Peterburg! U menia eshcho est’ adresa, Po kotorym naidu mertvetsov golosa…. Ia na lestnitse temnoi zhivu, i v visok Udariaet mne vyrvannyi s miasom zvonok… Ia vsiu noch’ naprolet zhdu gostei dorogikh, Shevelia kandalami tsepochek dvernykh.